Wheelchair housing design guide - Horn, Michelle; Smith, Jacqui; Runnalls, Jacquel; Sheehan, Kate; Habinteg Housing Association .; Building Research Establishment . (London : Riba Publishing, 2018)
Filled with practical advice and design considerations, this invaluable guide provides all the information you need to design good quality, accessible housing for wheelchair users.
WorldShare provided record
Keywords: Dwellings -- Barrier-free design -- Great Britain; People with disabilities -- Housing -- Great Britain; Dwellings -- Standards -- Great Britain; Building laws -- Great Britain